Early growth and dry matter partitioning of yellow passion fruit as affected by time of application and method of poultry manure placement - Okorie Okoro Ndukwe; Ibeabuchi Uko; Stella Muojiama; Chinyere Ndukwe; Amanda Okoh; Paul Baiyeri (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Passion fruit cultivation and utilization is fast emerging in Nigeria. Poultry farms are increasing with the corresponding increase in poultry manure production which is relatively affordable by farmers. Two experiments were conducted to evaluate the effect of placement method and time of poultry manure (PM) application on early growth and dry matter partitioning of yellow passion fruit. Method PM placement methods were incorporation, top-dressing, bottom-dressing and split combination of top-and bottom-dressing while time of PM application comprised application at transplanting, 2, 4 and 6 weeks after transplanting (WAT). The experiments were laid out as completely randomized design, replicated five and six times, respectively for PM placement methods and time of PM application. Growth and dry matter yield were determined at two weeks' interval and 20 WAT, respectively. Results Longest vines (78.5 cm) were significantly (p <0.05) produced by plants that were grown in PM incorporated medium. Thickest stems (6.75 mm), highest number of leaves (66.4) and dry matter accumulation were recorded in plants that received PM as top-dressing followed by PM incorporation. Application of PM at transplanting resulted in longest vines (95.8 cm), highest number of leaves (69.5) and dry matter partitioning to leaves, vines and roots. Conclusion PM top placement performed best with respect to early growth parameters and dry matter accumulation followed by PM incorporation, hence PM top placement is recommended for production of vigorous passion fruit vines in container. Poultry manure should be applied at transplanting for vigorous vines and not delayed beyond 4 weeks after transplanting.